Beauty and the Good : Recovering the Classical Tradition from Plato to Duns Scotus (Book collections on Project MUSE., 2020)
"Seeking to provide a richer alternative to both the contemporary cult of beauty and appearance and the concomitant decline of real beauty, this book offers a systematic treatment of the relationship between beauty and the good by drawing from ancient (e.g., Plato, Aristotle, and others) and medieval (e.g., Aquinas, Bonaventure, Hugh of St. Victor, and others) thought in such a way as to bring together scholars in these traditions"--